Going concern audit opinion: an empirical study - Ardiani Ika Sulistyawati Ardiani Ika Sulistyawati; Yuliyanti Yuliyanti; Dian Triyani; Rr Lulus Prapti Nugroho Setiasih Surjanti (Institute of Computer Science (IOCS), 2023)
This studies is motivated by means of the existence of problems in the shape of gap phenomena within the form of discrepancies inside the outcomes of the evaluation regarding the path of the connection among the independent variables of the observe which encompass the preceding 12 months's audit opinion, company length, liquidity, profitability, and solvency with the dependent variable going problem audit opinion in manufacturing organizations listed on the Stock Exchange Indonesian Securities in 2016- 2020. This examine targets to observe the impact of the preceding year's audit opinion, enterprise size, liquidity, profitability, and solvency on going difficulty audit opinion in manufacturing groups listed on the Indonesia Stock Exchange. The studies was conducted with a quantitative research approach. This form of studies is descriptive research. The population in this research is one hundred sixty businesses and the full pattern is 32 manufacturing businesses listed on the Indonesia Stock Exchange 2016-2020. The variables associated with this studies are the preceding 12 months's audit opinion, company length, liquidity, profitability, and solvency and going difficulty audit opinion in production groups. Data analysis technique the usage of logistic regression. The outcomes showed that there has been a significant effect on the preceding year's audit opinion, profitability, and solvency variables on going issue audit opinion in production agencies, whilst the enterprise size and liquidity variables had no significant effect on going subject audit opinion in manufacturing companies listed at the Stock Exchange. Indonesia.